Insights Into the Redox Sensitivity of Chloroflexi Hup-Hydrogenase Derived From Studies in Escherichia coli: Merits and Pitfalls of Heterologous [NiFe]-Hydrogenase Synthesis - Dragomirova, Nadya; Rothe, Patricia; Schwoch, Stefan; Hartwig, Stefanie; Pinske, Constanze; Sawers, R. Gary (Frontiers in Microbiology, 2018)
The highly oxygen-sensitive hydrogen uptake (Hup) hydrogenase from Dehalococcoides mccartyi forms part of a protein-based respiratory chain coupling hydrogen oxidation with organohalide reduction on the outside of the cell. The HupXSL proteins were previously shown to be synthesized and enzymatically active in Escherichia coli. Here we examined the growth conditions that deliver active Hup enzyme that couples H2 oxidation to benzyl viologen (BV) reduction, and identified host factors important for this process. In a genetic background lacking the three main hydrogenases of E. coli we could show that additional deletion of genes necessary for selenocysteine biosynthesis resulted in inactive Hup enzyme, suggesting requirement of a formate dehydrogenase for Hup activity. Hup activity proved to be dependent on the presence of formate dehydrogenase (Fdh-H), which is typically associated with the H2-evolving formate hydrogenlyase (FHL) complex in the cytoplasm. Further analyses revealed that heterologous Hup activity could be recovered if the genes encoding the ferredoxin-like electron-transfer protein HupX, as well as the related HycB small subunit of Fdh-H were also deleted. These findings indicated that the catalytic HupL and electron-transferring HupS subunits were sufficient for enzyme activity with BV. The presence of the HupX or HycB proteins in the absence of Fdh-H therefore appears to cause inactivation of the HupSL enzyme. This is possibly because HupX or HycB aided transfer of electrons to the quinone pool or other oxidoreductase complexes, thus maintaining the HupSL heterodimer in a continuously oxidized state causing its inactivation. This proposal was supported by the observation that growth under either aerobic or anaerobic respiratory conditions did not yield an active HupSL. These studies thus provide a system to understand the redox sensitivity of this heterologously synthesized hydrogenase.